HERO (historical heritage board): inovasi media permainan edukatif berbasis augmented reality guna pengoptimalisasi nilai-nilai sejarah untuk meningkatkan budaya literasi siswa - Eka Tia Wardani; Muhammad Syamsuddin; Hesty Nada Pratiwi (Historiography: Journal of Indonesian History and Education, 2021)
A report from the World Economy Forum (WEF) states that the Indonesian government urges the importance of anticipating changes in the flow of technology that have an impact on all aspects of life, including economic, political, social, and cultural. Entering this era, the role of literacy culture is very important in life so that it makes the younger generation to learn it from an early age for smooth communication between countries. In addition, the loss of awareness of literacy culture is a threat to the younger generation (Tribun News, 2017). As the next generation of the nation, the author contributes the idea, namely Hero (Historical Heritage Board) as an educational game media designed in such a way by highlighting the resources in every region in Indonesia with a funny and interesting appearance. In addition, HERO is also designed using two combinations of manual and digital. It is said to be manual because it still uses a digital board and because it uses a smartphone to help apply the game. The research method uses research and development (research and development) or RnD in the field of education. The model used is ADDIE which stands for Analyze, Design, Develop, Implement and Evaluate. The design of this media includes the following stages: (1) needs analysis, (2) design, (3) product development, (4) implementation, (5) evaluation. Hero's goal is to improve literacy education, children's imagination power and facilitate learning. Therefore, through HERO, the younger generation of Indonesia can further optimize historical values and be ready to face the post-pandemic with a strong foundation of Indonesian history.Menurut Laporan dari World Economy Forum (WEF) menyatakan bahwa pemerintah Indonesia menghimbau pentingnya mengantisipasi perubahan arus teknologi yang berdampak pada seluruh aspek kehidupan tak terkecuali ekonomi, politik, sosial, serta budaya. Memasuki era ini, peran budaya literasi menjadi sangat penting dalam kehidupan sehingga menjadikan generasi muda untuk mempelajarinya sejak dini demi kelancaran dalam berkomunikasi antar negara. Di samping itu, lunturnya kesadaran budaya literasi menjadi ancaman bagi generasi muda (Tribun News, 2017). Sebagai generasi penerus bangsa penulis memberikan sumbangsih ide yaitu Hero (Historical Heritage Board) sebagai media permainan edukatif dirancang sedemikian rupa dengan menonjolkan sumberdaya di setiap daerah di Indonesia dengan tampilan yang lucu dan menarik. Selain itu, HERO juga didesain dengan menggunakan dua perpaduan antara manual dan digital. Dikatakan manual karena masih menggunakan papan dan digitial karena menggunakan smartphone untuk membantu mengaplikasikan permainannya. Metode penelitian menggunakan penelitian dan pengembangan (research and development) atau RnD dalam bidang pendidikan. Model yang digunakan adalah ADDIE yang merupakan singkatan dari Analyze, Design, Develop, Implement dan Evaluate. Perancangan media ini meliputi tahap: (1) analisis kebutuhan, (2) desain, (3) pengembangan produk, (4) Implementasi, (5) Evaluasi. Tujuan Hero untuk dapat meningkatkan pendidikan literasi, daya imajinasi anak dan mempermudah pembelajaran. Maka dari itu, melalui HERO ini generasi muda Indonesia dapat semakin mengoptimalisasikan nilai-nilai sejarah dan siap menghadapi pasca pandemi dengan fondasi sejarah Indonesia yang kuat.